ANALISIS YURIDIS PELAKSANAAN SISTEM PEMBEBANAN PEMBUKTIAN TERBALIK TINDAK PIDANA KORUPSI PENGADILAN TINDAK PIDANA KORUPSI - MUHAIMIN, MUHAIMIN (Dinamika Hukum, 2018)
Proof is the central point of court in a court case. Proof is also a provision that regulates the instruments of evidence that are justified by the law and which the judge may use to prove the guilt of the indictment. Corruption is classified as an extraordinary crime (extra ordinary crime). the application of the reverse verification system does indeed appear to be something that ties with human rights. The application of a reversed evidentiary system should be placed in the context of a balance between the rights of the defendant and the rights of all the people. The problems studied in this research are: (1) How to Conduct Proof of Corruption in Corruption Court? (2) What are the Constraints Constraints faced in Corruption Proofing in Corruption Court in Corruption Court? The research method used in this research is qualitative research and descriptive research type with empirical juridical approach. Data analysis method used in this research is data collection, data reduction, data presentation, conclusion. Result of the research: (1) reverse proof is a deviation from the provisions of KUHAP which determines that the prosecutor is obliged to prove the criminal act, open the defendant. Under this provision the defendant can prove that he is not committing a criminal act of corruption. If the defendant can prove it does not mean he is not proven to be corrupt, because the prosecutor is still obliged to prove his indictment. (2) Lack of equality of perception of law enforcers in applying and performing reverse verification In practice in Corruption Court, reversed proof is applied depending on what is in the indictment of the prosecutor, as long as the prosecutor does not indict anything related to reverse verification then the Panel of Judges there is no basis for doing reverse proof. The conclusion of this research is: If the defendant can prove it does not mean he is not proven to be corrupt, because the public prosecutor is still obliged to prove his indictment. Suggestions of this research are: Improvement of the contents and weaknesses of Law Number 20 Year 2001 on Amendment to Law Number 31 of 1999 on Eradication of Corruption. Keywords: Corruption, reversed proof, Corruption Court